Ultrasound-responsive phase-transitional nanomedicine enables intensity-tunable postoperative analgesia - Song, Xinye; Feng, Miao; Chen, Hao; Luan, Yong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionEffective handling of pain after surgery is a major clinical issue, since insufficient pain relief is associated with extended recovery, excessive opioid use, and increased healthcare. Current approaches are limited by the short duration of local anesthetics, opioid-related adverse effects, and the lack of dynamic adjustability in pain relief. Here we report a theranostic nanoplatform, Rg3-liposomes@DMSN-levobupivacaine-PFP (RDLP), which integrates ultrasound-triggered phase transition, contrast-enhanced ultrasound (CEUS) imaging, and intensity-tunable drug release to address these limitations.MethodsRDLP features a core-shell architecture: dendritic mesoporous silica nanoparticles (DMSN) encapsulate the local anesthetic levobupivacaine and the phase-transition agent perfluoropentane (PFP), with a biocompatible Rg3-liposome coating enhancing stability and reducing drug leakage. Upon ultrasound irradiation, PFP undergoes liquid-to-gas phase transition, generating microbubbles that amplify CEUS signals for real-time visualization of drug distribution and drive inertial cavitation to trigger burst release of levobupivacaine. This design achieves high levobupivacaine encapsulation efficiency and enables spatiotemporally controlled release, with ultrasound accelerating drug release kinetics in vitro.ResultsRDLP combined with ultrasound prolonged analgesia compared to free levobupivacaine and enabled on-demand adjustment of pain relief intensity via multiple ultrasound irradiation cycles, restoring paw withdrawal thresholds and latencies to near-baseline levels in vivo. The platform exhibits exceptional biocompatibility, with no histopathological damage to sciatic nerves.DiscussionRDLP bridges imaging guidance and therapeutic intervention, leveraging ultrasound’s deep tissue penetration and Rg3’s natural biocompatibility to overcome limitations of conventional nerve blocks and ultrasound-responsive systems. This non-invasive, adjustable strategy offering potential to reduce opioid reliance and improve patient outcomes in perioperative care.